Developing an improved seizure diary as a monitoring tool for epileptic patients in South Africa - Egenasi, Chika Kennedy (University of the Free State, 2023)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱 Epilepsy is a debilitating disease with a high risk of morbidity and mortality globally. A seizure diary is one of the methods described in the literature that can be used to manage patients living with epilepsy. These diaries are available in two formats, paper-based and electronic diaries. This study aimed to develop an improved seizure diary and determine patients’ perception of its use in the management of patients with epilepsy in South Africa. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀 In the first phase of this study, a scoping review of literature was performed. An extensive search of appropriate literature was conducted using online databases, such as MEDLINE, Scopus, CINAHL, Cochrane and EBSCOhost. Key phrases, such as seizure diary, paper diary, and seizure tracker, were used to identify and retrieve relevant themes, categories, and subcategories of literature for examination. In the second phase of the study (a cross-sectional study), cohorts of patients with epilepsy were identified at the casualty and local clinics of a hospital in Kimberley, and the neurology specialist epilepsy clinic in Bloemfontein. Questionnaires were distributed to patients, to gather data on their perceptions of and attitudes to the epilepsy diary, and their opinions on what must be included in a seizure diary. The third phase of the study involved a modified Delphi survey with a panel of 10 local and two international experts, who deliberated on what they believed were the required contents of a seizure diary. In the fourth phase, a longitudinal study, a new seizure diary was developed, based on the suggestions of the expert Delphi panel and the recommendations of patients living with epilepsy. The new seizure diary was distributed to patients who had completed the initial questionnaire, and they were requested to use it for six months. In phase 5a (cross-sectional study), patients, relatives, and caregivers (participants) were requested to complete a questionnaire about their experiences of the new seizure diary. Finally, in phase 5b, a final version of the new seizure diary was designed. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀 In phase 1, 1 125 articles were identified from the database search, of which 23 were selected for review by the study. In phase 2, 182 patients with epilepsy were recruited for the study, 65 were patients who had previous exposure to a seizure diary, and 117 were unexposed. Of the patients who had previous exposure to the seizure diary, 64 (98.5%) found the diary useful, but 15 (23.1%) reported facing various challenges with using the seizure diary. In phase 3, the modified Delphi survey had three rounds, with 12 expert panellists completing each round. Consensus for any item was set at 70%. Eighteen items were suggested as the required contents of a seizure diary. The seizure diary, designed in phase 4, was distributed to 139 patients (81 previously diary-unexposed and 58 who had previous exposure to a seizure diary) to use for six months. In phase 5a, of the 139 patients who received the new seizure diary,100 (67 previously diary-unexposed participants and 33 participants who had previous exposure to a seizure diary) completed questionnaire 2. Participants who had previous exposure to a seizure diary were predominantly very positive about the new diary because it had more information. However, 21.2% preferred the old one, because it was easier to complete. In phase 5b of the study, the final draft of the new seizure diary was designed for use by patients with epilepsy. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻 An expert panel of specialists, patients, caregivers, and relatives participated in developing a new seizure diary. Despite a few patients reporting that they preferred the old seizure diary, most participants preferred the new seizure diary and were willing to use it.
Thesis (Ph.D.(Family Medicine))--University of the Free State, 2023
Keywords: Epilepsy; Seizure diary; South Africa; Clinics; Modified delphi; Experience; Perceptions; Attitudes; Unexposed; Previously exposed